What's new in endobronchial ultrasound for mediastinal staging?. Issue 4 (July 2020) - Marcoux, Mathieu; Ost, David E.
Abstract : Purpose of review: The essential role of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in lung cancer diagnosis and staging is now well established. With a growing body of evidence seen over the last decade, the objective of this article was to review the newest findings, provide evidence-based guidance to clinicians and identify areas for future research related to EBUS-TBNA and staging in lung cancer. Recent findings: Recent literature regarding EBUS-TBNA for lung cancer staging was reviewed, with a focus on evidence published subsequent to the 2016 guideline on technical aspects of EBUS-TBNA by the American College of Chest Physicians (ACCP). New findings were reported for the following: role of rapid on-site cytological evaluation (ROSE), needle size, lymph node ultrasound characteristics, molecular testing, as well as practice patterns and gaps in quality of care. Summary: Significant advances in EBUS-TBNA have been realized since the publication of the 2016 ACCP guideline. Future areas of investigation have been identified and will require collaboration between centers of expertise. Additional work will be required to translate these technological advances into improved value-based care in the lung cancer population.